Law and Bioethics : Intersections Along the Mortal Coil. - Smith II, George P. P. (Taylor and Francis, 2012)
George P. Smith, II is a leading figure in the world of medical law and ethics. During his long career he has addressed some of the most important issues in bioethics and has contributed much original thought to debates in the field. This book celebrates his contribution to scholarship in this area and brings together his key writings in bioethics. The chapters include previously published material which has been substantially updated to reflect recent developments in medicine and law. The book covers topics such as: human rights and medical law; the allocation of resources and distributive ju.